Electrocardiographic changes in awassi diarrheic suckling lambs in Iraq: اسلام جواد الخفاجي وعلاء كامل محمود - . Alkhafaji, Islam Jawad; Mahmood, Alaa Kamil (The Iraqi Journal of Veterinary Medicine, 2019)
This study was done to investigate the electrocardiographic changes in 90 diarrheic nursed Awassi lambs, in comparison with 10 clinically healthy lambs of the same breed. Their ages were ranged from 5 days to 2 months, in Karbala City-Iraq, from November 2015 to April 2016. The diarrheic lambs showed significant (P≤0.05) decreased duration of P-wave (0.039±0.0000001 ms and shorter QRS wave amplitudes 0.6 0±0.042 mV with duration 0.041±0.0008 ms , higher T wave amplitude and duration ( 0.25±0.034 mV and 0.070±0.002 ms) , prolonged QT (0.21±0.004 ms) but ST-segment ( 0.17±0.004 ms) were its observed sinus arrhythmia with tachycardia in lead-II in diarrheic lambs were recorded compared with non-diarrheic lambs group which their QRS duration and amplitude were it was (0.04±0.000001ms and 0.65±0.026 mV ) , T waves duration and amplitude were ( 0.076±0.004 ms and 0.21±0.012 mV ) QT interval (0.20±0.011 ms) and ST-segment ( 0.16±0.011 ms) .The morphological abnormal of ECG changes in diarrheic suckling lambs characterized by a widening or flattening, bifid(mitral) and pulmonale (tall) shape of P wave, increased P-R interval, increased duration of QRS complex and QT-prolongation, ST-depression or elevation .Inverted or board (slurring) tall, symmetric, peaked shape of T waves. These abnormal shapes appeared alternately in lead I, II, III, aVR, aVL and aVF. Conclusively the diarrheic lambs showed serious abnormal changes of electrocardiography..